Letter - Negrín, Juan
1942-12-10 013-0008-001 J. NEGRIN Confidential December the 10th, 1942. My Dear Sir Walter I have just been informed that our friend Rodriguez Vega, Secretary of the U.G.T. (Union General de Trabajadores) has crossed from Spain into Portugal and is now at Lisbon under the name of Ramirez Villamil. I have good reasons for believing that he has been, in some way, helped by the British Intelligence Service at the request of the Spanish elements who are collaborating with them in their struggle against the nazi's agents in Spain. It is of the greatest urgency to get Rodriguez Vega out of Portugal, where he may be at any moment in the most serious danger of being arrested by the International Police and sent back to Spain. Unfortunatelly we know that that has been the fate of many of our countrymen who had been able to cross into Portugal. I am most anxious to see Rodriguez Vega before he goes to Mexico where his family is living; and I am sure it would be interesting from more than one point of view to make it possible for him to spend a few weeks in England. I do not think there is anybody in a better position than Rodriguez Vega to give a full Sir Walter Citrine, Transport House, Smith Square, LONDON. 292/946/13/8(i)